ANALISIS PENERAPAN SIKLUS AKUNTANSI PADA USAHA KECIL DAN MENENGAH DI KOTA LUBUKLINGGAU (STUDI KASUS DI KECAMATAN LUBUKLINGGAU UTARA I) - Kusnadi Yudha Wiguna; Dewi Ermawati (Jurnal AkunStie (JAS), 2019)
The purpose of this study was to determine the application of the accounting cycle to small and medium enterprises in the city of Lubuklinggau (case study in North Lubuklinggau District 1). Data analysis in this research is qualitative analysis. The population in this study were SMEs in North Lubuklinggau District 1 which totaled 370 SMEs with a sample of 80 respondents of SMEs in North Lubuklinggau District 1. The data in this study are primary data obtained directly from respondents whose sources are in the form of observations, interviews, and questionnaires. The results of the calculation of the answers to the questionnaire that has been distributed, namely with a weighted score of 1.53% where the Guttman scale is at 0% - 25%, namely no association or low association (weak association) means that SMEs do not apply the accounting cycle or the application of the accounting cycle is still very low / weak in the management of business finances, the application of the accounting cycle for SMEs only reaches the stage of recording transactions of 5% and 11.25% which have proof of transactions. The absence of an accounting cycle for SMEs is caused by the educational background of respondents and SMEs do not have adequate understanding and knowledge of accounting.